2020
DOI: 10.3389/fmicb.2019.02967
|View full text |Cite
|
Sign up to set email alerts
|

Trichostomatid Ciliates (Alveolata, Ciliophora, Trichostomatia) Systematics and Diversity: Past, Present, and Future

Abstract: The gastrointestinal tracts of most herbivorous mammals are colonized by symbiotic ciliates of the subclass Trichostomatia, which form a well-supported monophyletic group, currently composed by ∼1,000 species, 129 genera, and 21 families, distributed into three orders, Entodiniomorphida, Macropodiniida, and Vestibuliferida. In recent years, trichostomatid ciliates have been playing a part in many relevant functional studies, such as those focusing in host feeding efficiency optimization and those investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…The issue of whether “morphology or molecules” should primarily be taken into account within systematics of different groups of protists [ 43 , 44 ], and in particular, in ciliates [ 45 , 46 , 47 ] has been under debate for the last decade. Currently, molecular data are favored and seem to give more detailed results, although morphological traits are still extremely valuable and provide important complementary data [ 48 , 49 , 50 , 51 ]. While general appearance (i.e., cell shape and size) allows for quick and rough species assignment in Paramecium , type and number of MICs, along with the morphology of contractile vacuoles, are considered the most important discriminating fine traits of these ciliates [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The issue of whether “morphology or molecules” should primarily be taken into account within systematics of different groups of protists [ 43 , 44 ], and in particular, in ciliates [ 45 , 46 , 47 ] has been under debate for the last decade. Currently, molecular data are favored and seem to give more detailed results, although morphological traits are still extremely valuable and provide important complementary data [ 48 , 49 , 50 , 51 ]. While general appearance (i.e., cell shape and size) allows for quick and rough species assignment in Paramecium , type and number of MICs, along with the morphology of contractile vacuoles, are considered the most important discriminating fine traits of these ciliates [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the following years, new ophryoscolecids were discovered in several wild and domestic ruminant host species [revised in Cedrola et al, 2020]. Based on these first studies, Dogiel (1927) proposed the first classification for the family Ophryoscolecidae (Table S1).…”
Section: Historical Survey Of the Family Ophryscolecidaementioning
confidence: 99%
“…
They are mainly associated with ruminant herbivorous mammals and participate in several digestive processes of their hosts (Firkins et al, 2020). Accordingly, questions concerning the metabolism of these ciliates have been intensively studied (Firkins et al, 2020;Newbold et al, 2015), while questions about their systematics still remain poorly understood (Cedrola et al, 2020).Ophryoscolecids were discovered in the XIX century when Gruby and Delafond (1843) reported the occurrence of several "animalcules" inhabiting the stomach and intestines of herbivorous mammals. The authors did not describe or draw any of the species found.
…”
mentioning
confidence: 99%
See 2 more Smart Citations